STRATEGI PEMASARAN PRODUK MENGGUNAKAN MEDIA ANIMASI DI INDONESIA - Laksita, Ida Ayu Tara; Prasetya, Ni Kadek Novi Elita (Pusat Penerbitan LPPM ISI Bali, 2024)
In the growing digital era, the use of animation media has become one of the effective marketing strategies in Indonesia. Animation provides a visual appeal that is able to convey marketing messages in an attractive and easily understood manner by various audience segments. This research aims to analyse product marketing strategies that use animated media, with a focus on the effectiveness, flexibility, and consumer engagement generated. The research method used is qualitative analysis with case studies on several companies in Indonesia that have successfully adopted animation in their marketing campaigns. The results show that animation not only increases product appeal, but is also able to convey complex messages in a simpler and more interactive way. In addition, animation has also proven effective in building brand awareness and creating a strong emotional connection with consumers. This research is expected to provide insights for creative industry players and companies in optimising marketing strategies through the use of animation media.